Effect of oral silymarin on liver function in pediatric acute lymphoblastic leukemia in the maintenance phase: a double-blind randomized clinical trial - Eghbali, Aziz; Sadeghian, Mahnaz; Ghasemi, Ali; Afzal, Roghayeh Rahimi; Eghbali, Aygin; Ghaffari, Kazem (Frontiers in Pharmacology, 2024)
Liver dysfunction is one of the most common disorders in patients with acute lymphoblastic leukemia (ALL). In recent studies, silymarin has been observed to have hepatic protective effects. Therefore, in this study, the effect of oral silymarin on the hepatic functions of patients with ALL was investigated. In the present double-blind clinical trial study, 121 patients with ALL over 5 years of age were divided into two groups after obtaining informed consent. The subjects were randomly divided into a silymarin-treatment group and a placebo group. In the silymarin-treatment group, patients received 70 mg oral capsules of silymarin twice daily or syrup of silymarin three times a day (each 5 ml of syrup contains 50 mg of silymarin). Patients were examined once a month for 9 months to receive capsules and measure the levels of alanine aminotransferase (ALT), aspartate transferase (AST), alkaline phosphatase (ALP), gammaglutamyl transferase (GGT), bilirubin, albumin, and cholesterol. Comparison of changes before and after treatment in the two groups showed that receiving oral silymarin resulted in a slight significant decrease in the levels of ALT, AST, GGT, and bilirubin (P < 0.05), but had no effect on ALP, albumin, and cholesterol (P > 0.05). The results of the present study showed that in pediatric patients with ALL, silymarin intake improves liver function. The very strong antioxidant effect of silymarin may explain its protective effect on the liver.